The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.4049/jimmunol.178.1.211
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Negatively Regulates CpG-Induced IL-10 in Bone Marrow-Derived Dendritic Cells

Abstract: Dendritic cells (DCs) are important players in the regulation of Th1- and Th2-dominated immune responses. In these studies we showed that IFN-γ, the key mediator of Th1 immunity, actively suppressed the production of IL-10 in murine DCs when activated with LPS or CpG. Our analysis revealed that both LPS and CpG induced IL-10 and IL-12 production but that the presence of IFN-γ, in a dose-dependent manner, suppressed the production of IL-10 while enhancing that of IL-12. The observed inhibition of IL-10 producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 61 publications
3
18
0
Order By: Relevance
“…IFN-␥ signaling through VLP pulsed DCs promoted IL12 secretion, and DCs lacking the IFN-␥ receptor produce less IL-12 and increased amount of IL-10 upon stimulation with papillomavirus VLPs, or the TLR agonist zymosan. These data indicate that IFN-␥ signaling enhances induction by DCs of a Th1 type T cell response (27). Thus, IFN-␥ signaling via DC is unlikely to promote the inhibition of E7-specific CD8 responses in an Ag-experienced host.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…IFN-␥ signaling through VLP pulsed DCs promoted IL12 secretion, and DCs lacking the IFN-␥ receptor produce less IL-12 and increased amount of IL-10 upon stimulation with papillomavirus VLPs, or the TLR agonist zymosan. These data indicate that IFN-␥ signaling enhances induction by DCs of a Th1 type T cell response (27). Thus, IFN-␥ signaling via DC is unlikely to promote the inhibition of E7-specific CD8 responses in an Ag-experienced host.…”
Section: Discussionmentioning
confidence: 83%
“…Professional Ag presentation cells play a critical role in controlling the adaptive immune response, and can respond to IFN-␥. However, IFN-␥ negatively regulates IL-10 secretion by macrophages and dendritic cells (DCs) (26,27). To establish whether IFN-␥-mediated inhibition of induction of CD8 T cells might be mediated by a phenotypic change in DC, ϩ DCs (10 5 ) from C57BL/6 or IFN-␥R Ϫ/Ϫ mice were left exposed to 40 g/ml bovine PV virus-like particles (VLP) or 50 g/ml Zymosan for 18 h and supernatants were assayed for IL-10 and IL-12 by ELISA.…”
Section: Cd11c ϩ Cells From Ifn-␥ Receptor Knockout But Not Wild-typementioning
confidence: 99%
“…IL-1ß and IL-18 are proinflammatory cytokines secreted as proforms requiring caspase 1 cleavage for activation (14), and we observed an increase in caspase 1 expression in these tumors (unpublished data). Although bacterial CpG motifs are essentially known as potent inducers of proinflammatory cytokines such as IL-1ß and IL-18, production of the anti-inflammatory cytokine IL-10 was recently reported following CpG stimulation (15,16). These observations suggest the existence of a two-step model where the initial TLR signaling induced pro-inflammatory cytokines, and then IL-10, thereby influencing the ensuing immune responses (15).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to IFN induced down-regulation of IL-10 Flores et al have studied suppression of this cytokine in CpG stimulated dendritic cells (Flores et al, 2007) They suggested that Stat1 might be involved but the findings were difficult to interpret because IL-10 levels were decreased in Stat1-/-mice such that there was Our studies have demonstrated that suppression of the LPS-induced -1044 IL-10 promoter activity can be achieved when IFN is added simultaneously with LPS but a clearly stronger effect can be achieved when IFN is added at -2hs (see Figure 2). This finding is surprising given that LPS signalling leads to binding of Stat3 to the promoter only with slow kinetics, while IFN can induce strong Stat1 binding already at 1 h ( Figure 5A).…”
Section: Effect Of Ifn On Binding Of Stat1 and Stat3 In The Intact Numentioning
confidence: 99%